Enhancing Hematological Parameters and Alleviating Complaints in Transfusion-Dependent Thalassemic patients - Raheela Pyar Ali; Saad, Saadia; Sana Soomro; Sadia Arif; Asaad Javaid (Journal of Postgraduate Medical Institute, 2024)
Objective: To investigate the potential benefits of using supplements, such as folic acid, vitamin E, and calcium, to improve certain hematological parameters and overall well-being in patients with beta-thalassemia. Methodology: This quasi-experimental study included 277 transfusion-dependent beta thalassemia major patients aged 20-38 from 20th January-30th April 2024. Patients received at least one transfusion per month and presented symptoms like lethargy, fatigue, breathlessness, bone pain, brittle hair and nails. They were prescribed daily oral supplements: Folic Acid (5mg), Vitamin E (200mg), Calcium (500mg) with Vitamin D3 (400IU), and Magnesium (150mg). Patients were monitored every 15 days for symptom improvements. Blood samples were collected before each transfusion. Hematological parameters like hematocrit, hemoglobin levels, White Blood Cells (WBCs), Red Blood Cells (RBCs) and platelets were recorded. Hematological parameters before initiation of supplements and at 3 month follow-up were compared using paired t test. Results: The results showed a significant increase in hemoglobin, hematocrit, RBCs, and platelets after the intervention. Mean hemoglobin improved from 8.284 to 8.651, with increase of 0.367 units (95% CI: 0.24336 to 0.4904). MCV increased by 0.4224, and MCH by 0.2365, both statistically significant (p = 0.047 and p = 0.007, respectively). The generalized complaints reduced considerably in these patients. Conclusion: The study showed that prescribed supplements significantly improved hematological parameters in these patients and reduced their clinical complaints.